Karateristik Morfologi Bibit Cendana (Santalum album L.) yang Ditanam pada Cekaman air Tanah Alfisol dan Vertisol - Lenny M. Mooy; Muhammad Kasim; Donatus Kantur (Politeknik Pertanian Negeri Kupang, 2013)
The morphological characteristics of sandalwood (Santanum album L.) seed having water stresses at Alfisol and Vertisol soil. This research was conducted in Oebelo, Central Kupang Sub District, from March to October 2010. Soil and plant were analyzed at The laboratory of Assessment Institute for Agricultural Technology of East Nusa Tenggara Province. The objectives of this research were to investigate the morphological characteristics of sandalwood (Santanum album L.) seed having water stresses at Alfisol and Vertisol soil. Experimental design used factorial design based with random block designed, which consisted of two factors. The first factor was water stress (C) with 5 levels namely C0: without water stress (control); C1: one day water stress; C2: two days water stress; C3: three days water stress, and C4: four days water stress. The second factor was soil types (T) consisted of Alfisol soil (T1) and Vertisol soil (T2). Analysis of Varian (Anova) was used to analyse all of the effect of treatments. Multiple Range Duncan Test at 5% of significance level was used to compare the differences in the treatments. The result showed that one day water stress (C1) at Alfisol soil and two days water stress at Vertisol soil have higher morphological characteristics including; plant height, rod diameter, leaves wide, root surface area, the amount of haustorium and dry matter than other treatments. Key words: Sandalwood, morphology, water stress, alfisol and vertisol.